A novel lunar soil coring approach based on particle unidirectional flow effect to reduce drag and increase efficiency. Issue 1 (1st July 2021) - Chen, Huazhi; Li, Lifang; Cui, Yang; Jiang, Shengyuan
Highlights: A novel penetration coring method for lunar soil is proposed. The novel method improves coring efficiency a lot. Particles flow in the anti-gravity direction plays a decisive role. Asymmetric surface pattern contributes greatly in the particles flow. Abstract: Low disturbance lunar soil profile samples play an important role in the study of the evolution of the Moon and the exploration of lunar mineral resources. At present, two methods have been applied to collect lunar soil profile samples, namely drill coring (including rotary drilling and rotary-percussive drilling) and impact penetration coring. Among them, the impact penetration coring has little disturbance to the sample, but the high resistance and low filling rate limit its application prospects. In this study, the cause of the above problems was discussed and a method of reducing resistance and increasing efficiency based on the particle unidirectional flow effect was proposed. The particle unidirectional behavior was analyzed by employing the numerical simulation based on the discrete element method (DEM). Then the feasibility of this drag reduction and efficiency enhancement method was verified experimentally. The results show that the asymmetric wedge-shaped arrays on the inner and outer walls of the coring tube and the simultaneous application of a simple harmonic vibration (with a frequency of 50 Hz and amplitude of 0.6 mm) significantly improved the coring performance. Compared with the impact penetration coring, the specific energy consumption was reduced by 38.5%, the coring rate was increased by 16.4%, and the force required removing the coring tube after sampling was reduced by 84%. When the wedge-shaped arrays were replaced with the wheat awn arrays whose height was close to the median size of the simulated lunar soil particles, more particles were discharged. Compared with the impact penetration coring as well, the specific energy consumption was reduced by 48.6%, the coring rate was increased by 22.2%, and the force required removing the coring tube was reduced by 86.7%.